PENGARUH KEPEMIMPINAN, DISIPLIN KERJA , DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI DI DINAS PERHUBUNGAN KOTA BALIKPAPAN - Ea Gracia Tambuwun, Mayse; Hadiyatno, Didik; Arrywibowo, Imam (Fakultas Ekonomi Universitas Balikpapan, 2026)
The purpose of this study was to determine the influence of leadership, work discipline, and work environment on job satisfaction of Balikpapan City Transportation Agency employees. The method used in this study was statistical testing with primary data in the form of distributed questionnaires. Data analysis used Smart PLS. The results of this study indicate that the Leadership variable has a significant effect on job satisfaction of Balikpapan City Transportation Agency employees, the Work Discipline variable has no significant effect on job satisfaction of Balikpapan City Transportation Agency employees, and the Work Environment variable has a significant effect on job satisfaction of Balikpapan City Transportation Agency employees.